RECONSTRUCTION OF THE ARRANGEMENTS FOR THE FORMATION OF THE RED AND WHITE COOPERATIVE AS AN EFFORT TO ACHIEVE FOOD SECURITY IN INDONESIA - Zahro Zainna Sahida; Riana Susmayanti (Universitas Muhammadiyah Mataram, 2025)
This research discusses the reconstruction of regulations on the establishment of Koperasi Merah Putih as part of Indonesia’s food security strategy. The study uses a normative legal research method with a statute approach, analyzing relevant cooperative and food security regulations. Findings indicate that there is disharmony between Law No. 25 of 1992 on Cooperatives and Presidential Instruction No. 9 of 2025, which results in legal uncertainty in the establishment of cooperatives. The reconstruction should involve strengthening the legal framework through higher-level regulations such as Government Regulations or Presidential Regulations, while ensuring democratic principles of cooperatives are maintained. Moreover, notaries play a crucial role as gatekeepers in drafting authentic deeds to guarantee legal certainty and compliance.